Student's Environmental Literacy Profile Of Adiwiyata Green School In Surakarta, Indonesia - Hephi Meilinda; Baskoro Adi Prayitno; Puguh Karyanto (Intelektual Pustaka Media Utama, 2017)
Environmental literacy refers to the knowledge of the mechanism of how the nature works and the roles of human to preserve the nature sustainably. The dynamic relation between human and environment can be seen from the life interaction along with all the components. One characteristic of society that has environmental literacy is highly concerned with environmental. This research aims to analyze students’ environmental literacy in Adiwiyata Green School in Surakarta. Environmental literacy covers some components including environmental knowledge, attitude, and environmental concern.This research was developed through descriptive qualitative design to obtain data by employing classroom observation and questionnaire based on environmental literacy to the students in Adiwiyata Green School in Surakarta. The research finding shows that (1) students’ environmental literacy in Adiwiyata Green School in Surakarta is categorized as low level. Data obtained from the instrument are 77,38% for environmental knowledge, 59,50% for attitude, 70,12% for environmental concern. The average percentage for all components is 68,97%. Based on the finding, it can be concluded that the environmental literacy is still low. It can be seen from (1) knowledge and concern aspects are higher than attitude aspect, (2) attitude aspect contains two components which are anti anthropocentrism and anti-exemptionalism, so that it is necessarily to increase students’ concern toward the environment.